THE ROLE OF PHYSICAL EXERCISES IN THE DEVELOPMENT OF THE PHYSICAL QUALITIES OF FOOTBALL PLAYERS - Jahbarov Abulfayz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the manifestation of physical qualities in football players, from the physiological point of view, the ability to transmit excitation impulses in nerve fibers, the speed of muscle contraction, and the most important information related to the speed of time communication between the necessary centers in the cortex of the cerebral hemispheres.